2014
DOI: 10.1038/onc.2014.253
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y receptor Y5 as an inducible pro-survival factor in neuroblastoma: implications for tumor chemoresistance

Abstract: Neuroblastoma (NB) is a pediatric tumor of neural crest origin with heterogeneous phenotypes. While low stage tumors carry a favorable prognosis, over 50% of high risk NB relapses after treatment with a fatal outcome. Thus, developing therapies targeting refractory NB remains an unsolved clinical problem. Brain-derived neurotrophic factor (BDNF) and its TrkB receptor are known to protect NB cells from chemotherapy-induced cell death, while neuropeptide Y (NPY), acting via its Y2 receptor (Y2R), is an autocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 61 publications
9
60
0
Order By: Relevance
“…Moreover, the high ambient calcium concentration present during bone resorption or stiffness of the bone tissue may change tumor cell properties [36]. In the case of NPY, such an increase in its expression may be driven by brain-derived neurotrophic factor (BDNF), which is abundant in the bone environment and has been shown to induce NPY expression and release [37, 38]. In our model the local bone invasion and interaction of tumor cells with bone components is a secondary event, which provides a plausible explanation for the predominance of bone environment-independent pulmonary metastases in mice bearing TC71 xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high ambient calcium concentration present during bone resorption or stiffness of the bone tissue may change tumor cell properties [36]. In the case of NPY, such an increase in its expression may be driven by brain-derived neurotrophic factor (BDNF), which is abundant in the bone environment and has been shown to induce NPY expression and release [37, 38]. In our model the local bone invasion and interaction of tumor cells with bone components is a secondary event, which provides a plausible explanation for the predominance of bone environment-independent pulmonary metastases in mice bearing TC71 xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…It involves in a variety of neural and molecular events and plays an important role in both brain development and synaptic plasticity (Hong et al 2011). Recently, BDNF has been reported to be associated with tumor progression in several human malignancies, such as neuroblastoma (Czarnecka et al 2014), lung cancer (Okamura et al 2012), breast cancer, and colon cancer (Yang et al 2012(Yang et al , 2013. BDNF and its receptor, TrkB, are commonly upregulated in a variety of human tumors (Guo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…under hypoxic conditions (Tab. 1) (Czarnecka et al, 2015; Kitlinska et al, 2005; Lu et al, 2010). Further studies revealed a crucial role for both pathways in different aspects of neuroblastoma biology.…”
Section: Neuroblastoma and Ewing Sarcoma As Models Of Npy-rich Tumorsmentioning
confidence: 99%
“…Moreover, treatment with Y2R antagonist resulted in an induction of apoptosis mediated by BCL-2-interacting mediator of cell death (Bim), the pathway known to be activated in response to growth factor withdrawal (Lu et al, 2010). The proliferative effect of the constitutively active NPY/Y2R axis was further enhanced in the presence of Y5R, which was expressed in some neuroblastoma cell lines in an inducible manner (Czarnecka et al, 2015; Kitlinska et al, 2005). This phenomenon is in line with known interactions between NPY receptors that have been shown to enhance cell sensitivity to the peptide and augment its effects (Gehlert et al, 2007; Movafagh et al, 2006; Pons et al, 2008).…”
Section: Npy In Regulation Of Tumor Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation